BEYOND THE APPLICATION OF EDMODO IN CLASSROOM: STUDENTS’ PERCEPTIONS AND THEIR BARRIERS IN THE PROCESS OF UTILIZING IT IN WRITING CLASS - Siti Maria Ulfa; Susanto Susanto; Oikurema Purwati (Universitas Muhammadiyah Makassar, 2020)
This research was done to investigate the students’ perceptions and barriers in using Edmodo in their writing class. Besides, the barriers can be also the main points within the implementation of their writing class process. Edmodo is a free and secure learning platform that can be used in all lesson especially in university. It provides a very simple ways and simply make good pathway for teachers and students to communicate for a particular lesson especially for writing because the constructive comments were already stated within the platform. Since the focuses are perceptions of the students, a qualitative method was used through the use of documentation and interview were utilized to gather data. The findings showed that they strongly agreed that Edmodo very helpful in writing class, they can directly obtain the feedback, save their data safely and they can read it after a while and the rest perceptions will be explained more clearly.